2014
DOI: 10.1386/cjmc.5.1.87_1
|View full text |Cite
|
Sign up to set email alerts
|

The politics of transnational affective capital: Digital connectivity among young Somalis stranded in Ethiopia

Abstract: This article presents an explorative qualitative case study of how sixteen young Somali migrants stranded in Addis Ababa, Ethiopia feel about staying in touch with loved ones abroad using Internet-based transnational communication. Left-behind during transit migration from Somalia to overseas, at this moment they can only digitally connect with contacts living inside for example dreamed diasporic locations in Europe. Based on in-depth interviews, a focus group and concept maps drawn by informants the ambivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 19 publications
2
79
0
1
Order By: Relevance
“…A substantial amount of critical scholarship has emerged that probes the cultural politics of affectivity (Ahmed 2004(Ahmed , 2010Brennan 2004;Fortunati & Vincent, 2009;Jones, Jackson & RhysTaylor, 2014;Leurs, 2014a;Sedgwick, 2003;Turan Hoffman, 2014). However, affectivity remains understudied in migration and media studies: most previous research "on migration rarely captures the affective and emotional dimensions of global processes" (Boehm & Swank, 2011, p. 1).…”
Section: Affective Geographies On Youtubementioning
confidence: 99%
See 3 more Smart Citations
“…A substantial amount of critical scholarship has emerged that probes the cultural politics of affectivity (Ahmed 2004(Ahmed , 2010Brennan 2004;Fortunati & Vincent, 2009;Jones, Jackson & RhysTaylor, 2014;Leurs, 2014a;Sedgwick, 2003;Turan Hoffman, 2014). However, affectivity remains understudied in migration and media studies: most previous research "on migration rarely captures the affective and emotional dimensions of global processes" (Boehm & Swank, 2011, p. 1).…”
Section: Affective Geographies On Youtubementioning
confidence: 99%
“…The specific situation of the generation of young people born in the diaspora -descendants of those who have migrated -demands more attention (Wessendorfer, 2013), and especially their digital media use has been largely left unaddressed (Green & Kabir, 2012). Earlier work has shed light on how migrants use ICTs for transnational communication purposes with people in their country of origin (e.g., Georgiou, 2006;Leurs, 2014a;Miller & Slater, 2000;Vertovec, 2009). Besides transnational Skype and MSN Messenger conversations between the near and far connecting those who have migrated, those who have stayed and those in the diaspora, my focus on the particular configurations of age and generation revealed that second-generation migrant youth who are born in the diaspora were more concerned with the digital remediation of diaspora as an affective, symbolic marker.…”
Section: Transdisciplinary Dialoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…The digital co-presence of dispersed loved ones can play an important motivational role in enduring hardships in transit and for staying hopeful towards better futures elsewhere (Leurs, 2014(Leurs, , 2016Twigt, 2018). Meanwhile virtual practices provide asylum-seekers in Germany crucial ways of presenting themselves as the person they want to be or become, rather than the one that is being restricted by a lack of opportunities: as such it is the process of unbecoming a victimized refugee (Witteborn, 2015).…”
Section: For(e)dialoguementioning
confidence: 99%